2019
DOI: 10.18203/issn.2455-4510.intjresorthop20192676
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effect of per operative intravenous injection of tranexamic acid in patients undergoing arthroscopic anterior cruciate ligament reconstruction

Abstract: <p class="abstract"><strong>Background:</strong> Anterior cruciate ligament (ACL) tear is a common injury sustained during contact games hampering performance of the sportsmen and thus requires promt management. Arthroscopic ACL reconstruction is commonly associated with postoperative knee effusion which affects the functional recovery. Various treatment modalities are available for managing effusion after ACL reconstruction, which are associated with various grades of success and side effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(32 citation statements)
references
References 14 publications
2
30
0
Order By: Relevance
“…All the included RCTs reported on the number of patients requiring postoperative knee aspiration. 11,[19][20][21][22] Our pooled data revealed that patients randomised to TXA was associated with lower incidence of needing knee aspiration than the placebo group (studies ¼ 5, patients ¼ 580, OR: 0.19 [95% CI, 0.08 to 0.46], p ¼ 0.0002; I 2 ¼ 0%).…”
Section: Secondary Outcomesmentioning
confidence: 77%
See 4 more Smart Citations
“…All the included RCTs reported on the number of patients requiring postoperative knee aspiration. 11,[19][20][21][22] Our pooled data revealed that patients randomised to TXA was associated with lower incidence of needing knee aspiration than the placebo group (studies ¼ 5, patients ¼ 580, OR: 0.19 [95% CI, 0.08 to 0.46], p ¼ 0.0002; I 2 ¼ 0%).…”
Section: Secondary Outcomesmentioning
confidence: 77%
“…Four RCTs with a total sample size of 532 patients examined the postoperative blood loss in the arthroscopic ACRL surgery. 11,[19][20][21][22] Our analysis demonstrated that the use of intra-articular or intravenous TXA reduced approximately 80 ml of postoperative blood loss in comparison to the placebo group (MD: À81.93 ml [95% CI À141.80 to À22.05], p ¼ 0.007). However, statistical heterogeneity was observed as substantial (I 2 ¼ 95%).…”
Section: Primary Outcomementioning
confidence: 78%
See 3 more Smart Citations